Anion binding and fluoride ion induced conformational changes in bisurea receptors. (22nd January 2020) - Shu, Xi; Fan, Yu; Li, Shoujian; Jin, Yongdong; Xia, Chuanqin; Huang, Chao
Abstract : Two types of bisurea receptors, containing either 2, 6-substituted phenyl or 2, 6-substituted pyridine, are prepared, and their anion binding properties are investigated. Abstract : Two types of bisurea receptors, containing either 2, 6-substituted phenyl or 2, 6-substituted pyridine, are prepared, and their anion binding properties are investigated. Compared with the phenyl bisurea receptors, the pyridine bisurea receptors can be more easily converted to a cis – cis conformation from a trans – trans conformation, providing a cavity that more closely matches the volume of a fluoride ion and increasing the number of NH sites bound to the fluoride ion. As a result, the pyridine bisurea in cis – cis conformation shows stronger affinity and higher selectivity to fluoride ions, which is supported by crystal structure analysis and NMR titration experiments. Through DFT calculations, a mechanism of fluoride ion induced conformational changes of pyridine bisurea receptors is proposed, and the energy barriers of conformational changes for both types of receptors are determined.